130 Individual Differences in Skin Temperature Responses to Cold Pressor Stress During Sleep Restriction and Circadian Misalignment. (3rd May 2021) - Linton, Sabrina; Sprecher, Kate; Depner, Christopher; Burke, Tina; Dorrestein, Pieter; Fleshner, Monika; Knight, Rob; Lowry, Christopher; Turek, Fred; Vitaterna, Martha; Wright, Kenneth
Abstract: Introduction: Individual differences in cognition during sleep restriction and circadian misalignment have been shown to be trait-like. Here we explored the consistency of individual differences in cardiovascular responses to the cold pressor test (CPT) measured by changes in the distal-proximal skin temperature gradient (DPG) using the contralateral hand to that immersed in the ice water bath, which reflects a reflex cutaneous vasoconstriction. Methods: Eighteen healthy participants (8 females) mean (±SD) age 25.28 (±4.3), underwent two identical in-laboratory combined sleep restriction and circadian misalignment protocols preceded by an 8h baseline in-laboratory sleep opportunity. The participants were given a 3h sleep opportunity on night 2 and a 3h sleep opportunity on days 3 and 4 followed by recovery sleep. The CPT occurred the morning after the baseline sleep opportunity and the morning before recovery sleep. Participants maintained a seated posture beginning 30 min prior to the CPT and skin temperature was assessed starting 15 min before until 45 min after the CPT. DPG (proximal=subclavicular; distal=hand palmar) data were averaged into 3 min bins. Changes in DPG from pre-CPT and 5 min post-CPT were assessed as the primary outcome using mixed-model ANOVAs. Intra-class correlation coefficients (ICC) were calculated to measure consistency of individual differences for DPG responses. Results: Mixed-model ANOVA revealed significant effects of time and combined sleep restriction and circadian misalignment on DPG during the CPT (both p<0.05), such that the DPG was wider (i.e., more negative) post-CPT and during sleep restriction and circadian misalignment. Participants showed moderately consistent DPG responses across visits 1 and 2 at baseline (ICC=0.59) and substantially consistent DPG responses during sleep restriction and circadian misalignment (ICC=0.67). Further, participants showed moderately consistent DPG responses when comparing changes between baseline and sleep restriction and circadian misalignment across visits (ICC=0.58). Conclusion: Findings support that combined sleep restriction and circadian misalignment is associated with sympathetic activation and that individual differences in the DPG response to cold pressor stress are consistent. Support (if any): Office of Naval Research MURI grant N00014-15-1-2809, NIH/NCATS Colorado CTSA Grant UL1TR002535